Enhancing Maritime Emergency Response through Integrated Problem-Based and Team-Based Training - M. Rizki Fadiansyah; Tri Cahyadi; Larsen Barasa (Meteor STIP Marunda, 2025)
This study investigates the integration of Problem-Based Learning (PBL) and Team-Based Training (TBT) within Basic Safety Training (BST) to enhance teamwork effectiveness during simulated maritime emergencies. Conducted through a qualitative, phenomenological approach at Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta, the research involved in-depth interviews with five trainees and two instructors, alongside direct observations. The findings demonstrate that the PBL-TBT model catalyzes a critical shift in trainee competence, moving from rigid procedural recall toward dynamic, adaptive problem-solving. Furthermore, the methodology fostered the development of shared mental models and non-verbal coordination, building collaborative resilience under high-stress scenarios. The research concludes that the synergistic application of PBL and TBT effectively bridges a critical gap in traditional maritime education by systematically developing the non-technical skills essential for modern seafaring. This evidence-based model offers a vital strategy for maritime training institutions seeking to improve safety outcomes and cultivate seafarers who are not only technically proficient but also skilled in teamwork and crisis management, thereby addressing a fundamental need within the global maritime industry.